1989
DOI: 10.1002/pola.1989.080270312
|View full text |Cite
|
Sign up to set email alerts
|

Quinone–amine polymers. II. 1,3‐bis(3‐aminophenoxy) benzene‐p‐benzoquinone oligomers

Abstract: SynopsisA novel oligomeric compound has been synthesized by reacting 1,3 bis-(3-aminophenoxy)benzene (APB) with p-benzoquinone. A dark reddish brown product has been characterized using W, IR, and N M R spectra, and elmental analysis. It, too, adheres to metals, as does another polyetheramine-p-benzoquinone polymer synthesized in Part I [ B o g . Org. Coating, 15, 63 (1987)], and becomes nonwettable after heat curing. However, its moisture adsorption is only 0.1% by weight, as against 3% for the latter product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…When chitosan films were incubated in methanol/buffer solutions containing both tyrosinase and hexyloxyphenol, the film changed from colorless to brown. Figure 3a shows a large increase in the absorbance of this film in the 350-nm region which is consistent with a reaction between the quinone and amino groups (Kaleem et al, 1989;Erhan, 1991, 1998;Yamamoto et al, 1990). Control films incubated with either hexyloxyphenol or tyrosinase did not change color upon incubation, and Fig.…”
Section: Chemical Evidence For the Covalent Modification Of Chitosansupporting
confidence: 69%
“…When chitosan films were incubated in methanol/buffer solutions containing both tyrosinase and hexyloxyphenol, the film changed from colorless to brown. Figure 3a shows a large increase in the absorbance of this film in the 350-nm region which is consistent with a reaction between the quinone and amino groups (Kaleem et al, 1989;Erhan, 1991, 1998;Yamamoto et al, 1990). Control films incubated with either hexyloxyphenol or tyrosinase did not change color upon incubation, and Fig.…”
Section: Chemical Evidence For the Covalent Modification Of Chitosansupporting
confidence: 69%
“…Natural and synthetic quinone–amine polymers have received considerable attention due to their unique properties and potential applications in various technical fields such as conducting materials, corrosion inhibitors for mild steels, and coating materials 1–6. Three kinds of novel poly(aromatic amino‐2,3‐pyridinedione) oligomers, including poly(4,4′‐methylenedianiline–2,3‐pyridinedione, PMDAP), poly(4,4′‐ethylene dianiline–2,3‐pyridinedione, PEDAP), and poly(4,4′‐sulfonyldianiline–2,3‐pyridinedione, PSDAP), have been synthesized by our cooperative work group.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the observed absorbance peaks at 305 and 350 nm cannot be attributed to either cresol or its quinone. It has been reported that the reaction of quinones with amines can result in the formation of Michael's-type adducts that have maximum absorptivities between 340 and 400 nm (Nithianandam and Erhan, 1998;Kaleem et al, 1989;Yamamoto et al, 1990). These observations suggest that binding to chitosan may be due to reactions between quinones and chitosan's primary amino groups.…”
Section: Reaction Of Phenol Vapors With Tyrosinase-coated Chitosan Filmsmentioning
confidence: 99%